2012
DOI: 10.1111/ejn.12094
|View full text |Cite
|
Sign up to set email alerts
|

Separate amygdala subregions signal surprise and predictiveness during associative fear learning in humans

Abstract: It has recently been suggested that learning signals in the amygdala might be best characterized by attentional theories of associative learning [such as Pearce-Hall (PH)] and more recent hybrid variants that combine Rescorla-Wagner and PH learning models. In these models, unsigned prediction errors (PEs) determine the associability of a cue, which is used in turn to control learning of outcome expectations dynamically and reflects a function of the reliability of prior outcome predictions. Here, we employed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 48 publications
10
84
1
2
Order By: Relevance
“…In line with earlier studies, we focused on transient, learning-related activity (31)(32)(33), which is supposed to decrease as soon as the associations are learned (31)(32)(33)(34) and the US is reliably predicted (35)(36)(37). We expected learning-related activity in the amygdala for delay conditioning and in the hippocampus for trace conditioning.…”
Section: Mri Analysismentioning
confidence: 71%
“…In line with earlier studies, we focused on transient, learning-related activity (31)(32)(33), which is supposed to decrease as soon as the associations are learned (31)(32)(33)(34) and the US is reliably predicted (35)(36)(37). We expected learning-related activity in the amygdala for delay conditioning and in the hippocampus for trace conditioning.…”
Section: Mri Analysismentioning
confidence: 71%
“…The algorithm also accounts for each participant's baseline propensity to take gambles. Learning in the favored algorithm is weighted by associability (10,11), and the choices made for each deck tend to persist (7) (see SI Appendix for details of all learning algorithms and a validation of the model comparison procedure).…”
Section: Resultsmentioning
confidence: 99%
“…Previous high-resolution fMRI studies (Table 1) reported involvement of corticomedial and CeM AG in various aspects of Pavlovian conditioning and instrumental processes (Boll et al, 2013;Prévost et al, 2011Prévost et al, , 2012Prévost et al, , 2013. However, because prior high-resolution fMRI literature did not report CeM activations in response to aversive visual stimuli, we must turn to animal experiments to gain greater insight into biological significance of our results.…”
Section: Differential Engagement Of the Amygdala Subnuclei Groups In mentioning
confidence: 92%
“…Furthermore, there are substantial variations in methodology used to localize intra-AG activations. Generally, two main references have been used: Mai (2008) anatomical atlas (Bach et al, 2011;Boll et al, 2011Boll et al, , 2013Gamer et al, 2010;Prévost et al, 2011Prévost et al, , 2012Prévost et al, , 2013 or Amunts et al (2005) probabilistic atlas of the human AG subnuclei (Ball et al 2007(Ball et al , 2009Frühholz and Grandjean, 2013;Grant et al, 2015;Roy et al, 2009;Styalidis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%